Interest in Unions and Associations in a Knowledge-Based Economy: Canadian Evidence - Raykov, Milosh; Livingstone, D. W. (Just Labour: A Canadian Journal of Work and Society, 2014)
This study analyzes the results of a 2010 national survey of Canadian non-managerial employees' membership and interest in worker organizations. This is the first general survey to include associations as well as unions. Profiles of membership and interest in unions and associations are presented, then demographic, organizational and attitudinal factors related to interest in joining these worker organizations are examined. The findings suggest that, in spite of some recent decline in union density, most Canadian non-managerial workers who are interested in collective representation are members of at least one of these organizations. The strongest interest in joining is expressed by those who are highly educated, poorly paid and feel underemployed-even if allowed some workplace "voice". The limited prior focus on unions needs to be expanded to attend to both unions and associations as worker-controlled vehicles of representation, particularly to identify strategic alliances with the growing numbers of professional employees.